The Chicken-and-Egg Dilemma of Adult Social Anxiety and Compulsive Social Media Use - Žiedelis, Arūnas; Bulotaitė, Laima; Kymantienė, Justina (Psichologija, 2025)
Background. Social media is characterized by a habit-forming virtual architecture, which leads some users to exhibit compulsive behavior. There are clear links between social anxiety and compulsive online behavior, but it is not evident whether social anxiety is a risk factor for compulsive behavior or a consequence of time spent on social media. Aim. This study aimed to investigate the longitudinal cross-lagged relationship between different types of social anxiety and compulsive social media use. Method. The longitudinal sample consisted of 220 social media users who filled out the questionnaire twice with an approximate interval of 8 months between the data points. Compulsive use of social networks and four types of social anxiety arising from content sharing, privacy concerns, interactions with unfamiliar persons, and negative evaluation were assessed. We tested for autoregressive and cross-lagged effects between key study variables using structural equation modeling. Results. The results revealed that initial interaction and self-evaluation anxiety predicted later compulsive social media use but not vice versa, compulsive use predicted later content-sharing anxiety but not vice versa, and there were no cross-lagged associations between compulsive use and privacy concern anxiety. Conclusion. Such results suggest that the chicken-and-egg dilemma between social anxiety and compulsive online behavior may have different solutions, depending on the specific forms of social anxiety. Theoretical and practical implications of the obtained results are also discussed.